2019
DOI: 10.1029/2019gl082637
|View full text |Cite
|
Sign up to set email alerts
|

Observations of a Kinetic‐Scale Magnetic Hole in a Reconnection Diffusion Region

Abstract: Magnetic holes have been widely observed in various space plasma systems. The origin of magnetic holes and their influence to background plasma are under debate. In this paper, we show a kinetic‐scale electron vortex magnetic hole in a nonideal region of an active X line, which was observed by the Magnetospheric Multiscale mission at the dayside magnetopause. Intense current and nonideal electric field in the electron frame were observed within the magnetic hole, which led to a strong energy dissipation. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…This nonideal electric field was primarily parallel to the ambient magnetic field, thus the energy dissipation was through the current and electric field in the field-aligned direction rather than the perpendicular direction. These were the classic features of the EDR (Burch et al, 2016b;Torbert et al, 2018;Zhong et al, 2019Zhong et al, , 2020Zhou et al, 2019;Zenitani et al, 2011), consistent with the MMS trajectory shown in Figures 2b and 2c. Electrons were heated significantly in the field-aligned direction, from 50 eV in the ambient plasma to 150 eV around this EDR (Figure 4g), meanwhile, MMS observed large-amplitude high-frequency parallel electric field fluctuations (Figure 4h), which suggests the strong correlation between electron heating and the large-amplitude parallel electric fields.…”
Section: 1029/2020gl090946supporting
confidence: 84%
See 1 more Smart Citation
“…This nonideal electric field was primarily parallel to the ambient magnetic field, thus the energy dissipation was through the current and electric field in the field-aligned direction rather than the perpendicular direction. These were the classic features of the EDR (Burch et al, 2016b;Torbert et al, 2018;Zhong et al, 2019Zhong et al, , 2020Zhou et al, 2019;Zenitani et al, 2011), consistent with the MMS trajectory shown in Figures 2b and 2c. Electrons were heated significantly in the field-aligned direction, from 50 eV in the ambient plasma to 150 eV around this EDR (Figure 4g), meanwhile, MMS observed large-amplitude high-frequency parallel electric field fluctuations (Figure 4h), which suggests the strong correlation between electron heating and the large-amplitude parallel electric fields.…”
Section: 1029/2020gl090946supporting
confidence: 84%
“…An intense out‐of‐plane electron jet V eM with a peak speed of ∼1,200 km/s was observed at the center of this current sheet, while V eN (Figure 3h) exhibits a small negative peak of ∼ −400 km/s. The correlated sign change of V eL and B N implies that MMS crossed an active X‐line (Øieroset et al., 2001; Oka et al., 2016; Torbert et al., 2018; Zhong et al., 2018, 2019). This was an asymmetric reconnection since the plasma density changes from 6 to 16 cm −3 across this current sheet.…”
Section: Three‐dimensional Secondary Electron‐scale Magnetic Reconnecmentioning
confidence: 99%
“…The coupling of KSMHs with whistler mode waves, including wave formation, dispersion, and growth rates, was also studied by Huang SY et al (2018, 2019). Zhong ZH et al (2019) reported a KSMH event associated with strong energy dissipation near the active X line at the dayside magnetopause. They suggested that the KSMH probably provided an additional channel for energy dissipation besides that of the electron diffusion region.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2a illustrates the MMS trajectory within the magnetopause reconnection exhaust inferred from the spacecraft observations. We focus on the region between the first two MFRs (Figure 2) where a secondary reconnecting current sheet is detected (Zhong et al, 2019). This secondary magnetic reconnection is responsible for the formation of 1e).…”
Section: Event Overviewmentioning
confidence: 99%